In Vitro Cytotoxicity and Anti-HIV Activity of Crude Extracts of Croton macrostachyus, Croton megalocarpus and Croton dichogamus - Terefe EM; Okalebo FA; Derese S; Muriuki J; Batiha GES (Dove Medical Press, 2021)
Ermias Mergia Terefe,1 Faith Apolot Okalebo,2 Solomon Derese,3 Joseph Muriuki,4 Gaber El-Saber Batiha5 1Department of Pharmacology and Pharmacognosy, United States International University-Africa, Nairobi, Kenya; 2Department of Pharmacology and Pharmacognosy, University of Nairobi, Nairobi, Kenya; 3Department of Chemistry, University of Nairobi, Nairobi, Kenya; 4Centre for Virus Research, Kenya Medical Research Institute, Nairobi, Kenya; 5Department of Pharmacology and Therapeutics, Damanhour University, Damanhour, AlBeheira, 22511, EgyptCorrespondence: Ermias Mergia Terefe Tel +254 746272742Email eterefe@usiu.ac.keIntroduction: Human immunodeficiency virus (HIV) affects the body's defense mechanisms and leads to a number of opportunistic infections which later cause fatality as a result of an acquired immunodeficiency syndrome (AIDS). More than half a million individuals have lost their life in 2020 due to this disease. Antiretroviral drugs have played a great role in improving the quality of life of HIV infected individuals. The side effects of these drugs coupled with resistance of the virus to the various regimens, necessitates the search for potentially new and effective antiretroviral medication. The objective of this study is to evaluate anti-HIV activity of crude extracts of three Croton plants.Methods: As part of our effort in screening anti-HIV medications, we evaluated the cytotoxicity and anti-HIV activity of three Croton species used as herbal medicine in Africa. Crude extracts of Croton macrostachyus, Croton megalocarpus and Croton dichogamus were tested for their replication inhibition activity against laboratory adapted strains HIV-1IIIB in Human T-lymphocytic MT-4 cell line.Results: Based on our findings, the crude aerial part extract of C. dichogamus displayed the highest anti-HIV activity by inhibiting 73.74% of viral induced cytopathic effect (CPE) at IC50 value of 0.001 + 0.00 μg/mL giving a selectivity index (SI) of 3116.0. In addition, the crude leaf extract of C. megalocarpus showed higher anti-HIV activity by inhibiting 74.65% of CPE at IC50 value of 0.05 + 0.03 μg/mL giving an SI of 571.3.Conclusion: Out of five extracts from three Croton species screened for anti-HIV activity using human T-lymphocytic MT-4 cells, the leaf extract of Croton megalocarpus and aerial part extract of Croton dichogamus could be considered as promising extracts as they display high antiviral activity with low toxicity and high selectivity index values. To investigate the active constituents responsible for the anti-HIV activity, chemical identification of the active constituents is now in progress in our laboratory. Since there is no previously reported anti-HIV activity for these plants, there is a great need to isolate the compounds responsible for the noted activity.Keywords: HIV, MT-4 cells, Croton macrostachyus, Croton megalocarpus, Croton dichogamus, cytotoxicity, antiviral activity